Leases: Back to the fundamentals - TAN, Pearl Hock-Neo, (Institutional Knowledge at Singapore Management University, 2015)
The long awaited lease accounting standard, that began with a project proposal in 2006 is finally on its way to becoming a reality. After issuing two exposure drafts followed by a fairly long period of re-deliberations, the International Accounting Standards Board (IASB) announced on 30 October 2015 that a final standard will be issued by the end of the year with an expected effective date of 1 January 2019 and early adoption permitted for entities which have also adopted IFRS 15 Revenue from Contracts with Customers. In short, leases for lessees will be on-balance sheet with exemptions made for short term leases and small asset leases. However, there is no change for lessor accounting with the dual model approach being retained. That said, there are still a number of issues that may be of interest to lessors. The definition of a lease and how one determines the lease term and lease payments are likely to change from the existing model. Although it seems like a very basic element in the whole structure, the definition of a lease has significant implications for lease accounting in totality. This article explains the definition and its implications for lessees and lessors as outlined by the IASB.